Macrophage-targeted, enzyme-triggered fluorescence switch-on system for detection of embolism-vulnerable atherosclerotic plaques - Narita, Yudai; Shimizu, Kosuke; Ikemoto, Keisuke; Uchino, Ryuji; Kosugi, Mutsumi; Maess, Marten B.; Magata, Yasuhiro; Oku, Naoto; Ogawa, Mikako (Journal of controlled release, 2019)
The development of atherosclerotic plaques is a critical step that can result in an arterial embolism. Therefore, detection of these vulnerable plaques is of clinical significance for the diagnosis of atherosclerosis. However, there are few imaging systems able to detect such plaques easily. In this study, we designed a new platform for near-infrared fluorescence (NIRF) imaging of macrophages in atherosclerotic plaques, one using both a liposomal DDS and an activatable fluorescent probe, and evaluated the utility of this imaging for the diagnosis of atherosclerosis. We first synthesized a fluorescent switch-on probe, Peptide-ICG2, which is optically silent under normal conditions but activated in the presence of the lysosomal enzyme, cathepsin B. To achieve macrophage-specific fluorescence activation, we encapsulated Peptide-ICG2 into phosphatidylserine-containing liposome (P-ICG2-PS-Lip), since the accumulation of phosphatidylserine receptor-bearing macrophages is characteristic of embolism-vulnerable plaques. The experiments using macrophage-like RAW264 cells in culture showed that P-ICG2-PS-Lip was selectively taken up into the cells and that significant fluorescence of the probe was observed. For NIRF imaging of the atherosclerotic plaques, P-ICG2-PS-Lip was intravenously injected into ApoE-knockout atherosclerotic model mice or WHHL rabbits, and the fluorescence at the aortae was imaged. The results indicated that ICG fluorescence could be successfully observed at the plaques on the artery walls. The results of the present study thus suggest that NIRF imaging using P-ICG2-PS-Lip would be useful for detecting embolism-vulnerable atherosclerotic plaques.